Anti-CD4 monoclonal antibody prevents chronic graft-versus-host disease in mice by inducing immune tolerance of CD8+ T cells and alleviating thymus injury - Wang, Ziwei; Li, Ruiqi; Fu, Weijia; Cheng, Hui; Zhang, Yan; Tang, Gusheng; Yang, Jianmin; Wang, Jianmin; Ni, Xiong (Frontiers in Immunology, 2024)
BackgroundChronic graft-versus-host disease (cGVHD) manifests with characteristics of autoimmune disease with organs attacked by pathogenic helper T cells. Recent studies have highlighted the role of T cells in cGVHD pathogenesis. Due to limited understanding of underlying mechanisms, preventing cGVHD after allogenic hematopoietic cell transplantation (HCT) has become a major challenge.Materials and methodsHere, we used a representative cGVHD model with the donor C57BL/6 to recipient BALB/c combination. Post-HCT, mice were treated with IgG or anti-CD4 monoclonal antibody. The severity of cGVHD was assessed by evaluating symptoms of cGVHD and histopathology examination (H&E) of target organs. Thymus gland damage and defects of the negative selection were assessed by analyzing the CD4+CD8+ double-positive thymocytes, cortical thymic epithelial cells and medullary thymic epithelial cells (mTECs). Immunotolerance of CD8+ T cells was assessed by detecting the expression of CD80, PD-1, GRAIL and IL-7Rα. Long-term cellular and humoral immunity associated with graft-versus-leukemia (GVL) effects were evaluated through detecting the percentage of CD4+ T cells, IgG, IgM and IgA concentrations, and performing tumor challenge experiment.ResultsDonor CD8+ T cells caused thymic epithelial cells damage and impaired negative selection in recipients, leading to generation of autoreactive T cells and causing cGVHD. Anti-CD4 mAb treatment promoted immune incompetence of thymus-infiltrating CD8+ T cells, facilitated recovery of CD4+CD8+ thymocytes and regeneration mTECs, and preserved negative-selection, but had no effects on the long-term cellular immunity and humoral immunity, resulting in preservation of GVL effect.ConclusionOur results indicate that anti-CD4 mAb therapy early post-HCT allows thymus recovery by inducing the immune tolerance of thymus infiltrated CD8+ T cells, thereby alleviating thymic epithelial cells damage, preserving negative selection, and preserving long-term GVL effect at the same time.